Analisis Persepsi Dukungan Keluarga (Perceived Family Support), Dukungan Tempat Kerja (Perceived Workplace Support) dan Kebijakan Keseimbangan Kehidupan-Kerja (Work Life Balanced) Terhadap Kinerja Karyawan: Study Pada Karyawan UMB BOGA Yogyakarta - Veri Widodo (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study is a partial replication of a previous study conducted by Mustikaningrum (2022) on “analysis of the influence of perceptions of family support, workplace support and work-life balance policies on employee performance with work-life balance as an intervening variable”. The object of this study is UMB BOGA Yogyakarta, and the subjects are employees as many as 91 respondents. While data analysis techniques using SEM, with IBM SPSS and AMOS tools. The results of this study is the perception of workplace support, work-life balance policies have a positive and significant effect on employee performance. And the perception of family support has no effect on employee performance.